Systematic Literature Review: Adversity Quotient Dan Kemampuan Pemecahan Masalah Pada Pembelajaran Matematika - Eki Sutisna; Novaliyosi Novaliyosi; Aan Hendrayana; Anwar Mutaqin (UNION : Jurnal Ilmiah Pendidikan Matematika, 2022)
The purpose of this research is to describe the effect and the correlation between adversity quotient (AQ) and mathematical problem solving abilities in senior high school. The research method is Systematic Literature Review (SLR). The steps of this research are develop research questions; selection criteria; developing the search strategy; the study selection process; coding studies; appraising the quality studies; and synthesis result. Based on the result of 147 articles, there are 32 articles that appropriate with the criteria. The result of this study shows that Argument Driven Inquiry, Ethnomatics Problem Based Learning, Scaffolding Problem Based Learning, Learning Cycle 7E through Mind Mapping, Thinking Aloud Pairs Problem Solving, Two Stay Two Stray and Discovery Learning can be the references of math learning because have positive effect for student’s abilities in understanding mathematical concept, problem solving ability, critical thinking, creative thinking, creative reasoning, learning achievement, self confidence, learning independence, and achievement motivation through AQ. The student’s problem solving abilities can be seen from the several types of AQ. The quitter  are students who give up easily, the camper are students who feel satiesfied quickly with the result, without checking the answer again, and the climber are students who never give up.